Potentiation of a recombinant oncolytic parvovirus by expression of Apoptin - Olijslagers, Sharon; Dinsart, Christiane; Rommelaere, Jean (Cancer gene therapy, 2001)
The oncotropic and oncolytic behaviors of certain autonomous rodent parvoviruses make them promising vectors for anticancer gene therapies. However, these parvoviruses are often not potent enough to kill all tumor cells equally well. With the aim of enhancing the intrinsic antitumor effect and the range of natural parvoviruses, a recombinant H1 parvovirus vector was constructed that produces the Apoptin protein, a tumor cell-specific, p53-independent, Bcl-2-insensitive apoptotic effector. We compared the apoptotic activity exerted by a recombinant hH1/Apoptin virus with that of a Green Fluorescent Protein (GFP)-transducing recombinant virus, hH1/GFP, in three human tumor cell lines differing in their susceptibility to wild-type parvovirus H1-induced killing. We found that in cells that were rather resistant to the basal cytotoxic effect of wild-type H1 or the GFP recombinant virus, a parvovirus that expressed Apoptin caused a pronounced, additional cytotoxic effect. In contrast to its enhanced cytotoxicity toward tumor cells, hH1/Apoptin virus was not more toxic to normal human fibroblasts than was the wild-type H1 virus. Taken together, these data indicate that enhancing the oncotropic behavior of wild-type H1 parvoviruses with the tumor-specific apoptotic potency of Apoptin should lead to an effective replicative parvoviral vector.
Gesehen am 15.02.2021